THE IMPORTANCE OF STYLE TEACHING FOR UNIVERSITY FOREIGN LANGUAGE STUDENTS - Saydivaliyeva, Barno (Журнал иностранных языков и лингвистики, 2023)
The subject and content of stylistics as a linguistic science have not yet been precisely defined, which is why stylistic problems are increasingly becoming the focus of linguists, philologists, and other specialists. Many linguists agree that stylistics is a department that studies the diversity of expressive means of language. Stylistics occupies a special position among the other linguistic disciplines.